Implications of Distributed Energy Development in Blockchain-Based Institutional Environment - Karno Diantoro; Dedeh Supriyanti; Ardi; Yulia Putri Ayu Sanjaya; Sri Watini (Aptisi Transactions On Technopreneurship (ATT), 2023)
This research focuses on the high urgency of utilizing Artificial Intelligence (AI) and the Internet of Things (IoT) to enhance Smart Tourism Destinations (STDs). The integration of AI and IoT technologies offers unprecedented opportunities to revolutionize various aspects of tourism, from personalized recommendations to real-time data collection. The research aims to provide a comprehensive analysis of the current state, challenges, and future direction of STDs in the context of AI and IoT integration. It explores various AI techniques and IoT-enabled data collection mechanisms that can enrich the traveler experience and improve destination management. However, challenges such as privacy and data security issues need to be addressed. The research also provides foresight into future technologies like Augmented Reality (AR) and Virtual Reality (VR) that can further enhance STDs. The ultimate goal is to contribute to the development of smarter, visitor-oriented tourism destinations. The research highlights the significance of AI in shaping STDs and emphasizes the importance of addressing ethical considerations, data quality, interpretability, and human-AI collaboration to ensure responsible and effective use of AI in the tourism industry.